Displacement of maxillary right second premolar caused by gutta percha filling in corresponding primary molar. Issue 1 (April 2018) - Naka, Shuhei; Kokomoto, Kazuma; Ohata, Jumpei; Okawa, Rena; Nomura, Ryota; Nakano, Kazuhiko
Abstract: Background: For pulp therapy in primary teeth, commonly performed in daily clinical practice, calcium hydroxide paste is widely used as a root canal filling material and typically resorbed by the permanent successor upon its emergence into the oral cavity. Case report: A 21-year-old female was referred to our clinic for detailed examination of a residual maxillary right primary second molar. After extracting that tooth, a material thought to be gutta percha was unexpectedly extirpated. Conclusion: We speculated that the material had prevented eruption of the permanent successor because of lack of resorption, leading to its displacement.